Gingival Cyst of the Adult: Report of an Inconspicuous Lesion Associated with Multiple Agenesis - Juliana Mançano Melhado Brod; Fabrício Passador-Santos; Andresa Borges Soares; Marcelo Sperandio (Case Reports in Dentistry)
Gingival cyst of the adult is a rare slow growing and asymptomatic lesion that arises from the rests of the dental lamina. The present report describes the case of a miniscule adult gingival cyst in the lower anterior gingiva in a 51-year-old male with agenesis of lower premolars and lateral incisors. This paper contrasts the literature concerning the differentiation between the gingival cyst of the adult and the lateral periodontal cysts as well as the possible misguided concept that the former may be such rare an occurrence.